9 Safety of Human Chorionic Gonadotropin Monotherapy for Men with Hypogonadal Symptoms and Testosterone >300 ng/dL. Issue 1 (1st April 2022) - Rainer, Q; Pai, R; Masterson, T
ABSTRACT: Introduction: Human chorionic gonadotropin (hCG) is homologous to luteinizing hormone (LH) and is known to stimulate endogenous testosterone (T) production and may be an option for testosterone replacement therapy (TRT). Current guidelines recommend TRT for men with two T levels <300 ng/dl and symptoms of low T. A challenging patient population are men with symptoms of low T who do not meet biochemical criteria for TRT as there are not current treatment recommendations. We hypothesize that hCG may be a safe and effective therapy for men with hypogonadal symptoms and T >300ng/dl. Objective: Our objective was to evaluate for symptom improvement and side effects of hCG monotherapy in men with hypogonadal symptoms and T >300 ng/dL. Methods: We retrospectively reviewed the charts of 31 men treated with hCG monotherapy for hypogonadal symptoms with a T average (latest two lab results) >300 ng/dL who had follow-up labs at least 1 month after initiation of hCG therapy. We evaluated changes in hormones [T, LH, follicle stimulating hormone (FSH), and estradiol], hematocrit (HCT), glycated hemoglobin (A1c), and prostate specific antigen (PSA). Results presented as means standard deviation. Student t-test was used to compare pre- and post-treatment values, significance was set at p=0.05. We also evaluated for incidence of thromboembolic events, including stroke, deep vein thrombosis, and myocardial infarction. Results: The average age of patients was 49.0±15.8 years with a BMI of 28.6±4.8 kg/m2. Average follow-up after starting hCG therapy was 292 days, range 77 to 857 days. Average weekly hCG dosage was 1500 IU. Serum T increased from 431.27±117.22 ng/dL to 461.05 ±185.19 ng/dL (p=0.61, n=31). No change was seen in FSH (6.79±10.85 to 7.12±12.07 mIU/mL, n=8), PSA (1.55±1.44 to 1.90±1.81 ng/mL, n=10), HCT (43.43±2.27 to 44.48±2.86 %, n=12), estradiol (27.44±6.92 to 30.63±10.25 pg/mL, n=8), or A1c (6.15±0.95 to 6.33±0.93 %, n=4). A statistically significant decrease was seen in LH (4.93±1.98 to 3.66±1.85 mIU/mL, n=11). When evaluated for improvement of erectile dysfunction (ED, n=22), low libido (n=25), and low energy (n=19), 86%, 80%, and 79% of patients reported improvement of each symptom, respectively. All patients with ED were noted to be on another medication or therapy specifically for ED. No thromboembolic events were observed. Conclusions: Weekly hCG dosing appears to safely improve hypogonadal symptoms even with baseline T levels >300 ng/dL. No changes were noted in HCT, PSA, A1c and no thromboembolic events were recorded. Disclosure: No